The Networked Infrastructure of Fossil Capitalism: Implications of the New Pipeline Debates for Environmental Justice in Canada - Scott, Dayna (Revue générale de droit, 2013)
A read of the critical geography literature on the concept of “networked infrastructures” generates two arguments in relation to the environmental justice implications of the new pipeline debates. First, the proposed coast-to-coast pipeline is likely to exacerbate existing environmental inequities in Canada. Conceiving of the crude oil in a pipeline as a material flow of commodified nature demonstrates that, at the end of the pipe, inputs of labour, technology and capital are required to convert the crude into useable forms of energy. This leads to a serious engagement with the communities at the ends of the proposed pipes. Here, I illustrate the type of analysis that is required with a preliminary examination of the expected environmental health impacts from increased refinery emissions in Sarnia, Montréal and Saint John. Second, the notion that pipelines, despite their vital effects, are fixed and durable installations of built infrastructure—lending a marked inertia to the routes they cement—produces intergenerational equity concerns in relation to fossil capitalism. These concerns are brought powerfully to the fore by activists under the banner of Idle No More. In fact, it is this growing indigenous resistance movement centered on lands and resources that best illustrates the obvious contradiction: the permanence of the pipelines on the landscape, once built, underscores the gravity of the choices we are weighing, just as the active resistance of indigenous people across the county reveals the inherent instability of the networked infrastructure.